Hydroxyurea therapy in sickle cell anemia patients aids to maintain oral fungal colonization balance - Salvia, Ana Carolina Rodrigues Danzi [UNESP]; Figueiredo, Maria Stella; Braga, Josefina Aparecida Pellegrini; Pereira, Daniel Freitas Alves [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Koga-Ito, C. Y. [UNESP] (Wiley, 2013)
Background: The aim of this study was to evaluate the frequency of Candida species and presence of lesions in the oral cavity of patients with sickle cell anemia (SS). Methods: The study included 30 patients diagnosed with sickle cell anemia and taking hydroxyurea for at least 90 days (SS/HU+); and 39 patients with sickle cell anemia and without hydroxyurea therapy (SS/HU-). Two control groups were constituted by healthy individuals matched to the test groups in age, gender, and oral conditions (C/HU+ for SS/HU+ and C/HU- for SS/HU-). Oral clinical examination and anamnesis were performed. Yeasts were collected by oral rinses and identified by API system. Antifungal susceptibility evaluation was performed according to the CLSI methodology. Data obtained for microorganisms counts were compared by Student's t test (SS/HU+ vs. C/HU+ and SS/HU- vs. C/HU-) using MINITAB for Windows 1.4. Significance level was set at 5%. Results: No oral candidosis lesions were detected. Significant differences in yeasts counts were observed between SS/HU- group and the respective control, but there were no differences between SS/HU+ and C/HU+. Candida albicans was the most prevalent species in all groups. Candida famata was observed both in SS and control groups. Candida dubliniensis, Candida glabrata, Candida krusei, Candida tropicalis, Candida pelliculosa, and Candida parapsilosis were observed only in SS groups. Most strains were susceptible to all antifungal agents. Conclusion: Hydroxyurea therapy seems to decrease candidal counts and resistance rate in sickle cell anemia patients. However, further studies should be conducted in the future to confirm this finding. Hydroxyurea therapy in sickle cell anemia patients maintains fungal species balance in oral cavity. © 2013 John Wiley & Sons A/S.
Keywords: Antifungals; Hydroxyurea; Microbiology; Oral cavity; Sickle cell anemia; hydroxyurea; adult; anamnesis; antibiotic sensitivity; antifungal susceptibility; Candida; Candida albicans; Candida dubliniensis; Candida famata; Candida glabrata; Candida parapsilosis; Candida tropicalis; clinical article; clinical examination; controlled study; cross-sectional study; female; fungal colonization; human; male; mouth lesion; Pichia anomala; prevalence; priority journal; sickle cell anemia